Low-Frequency vs. Theta Burst Transcranial Magnetic Stimulation for the Treatment of Chronic Non-fluent Aphasia in Stroke: A Proof-of-Concept Study - Chou, Ting-Yu; Wang, Jia-Chi; Lin, Mu-Yun; Tsai, Po-Yi (Frontiers in Aging Neuroscience, 2022)
Background Although low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) has shown promise in the treatment of poststroke aphasia, the efficacy of high-frequency rTMS (HF-rTMS) has yet to be determined. Purpose We investigated the efficacy of intermittent theta burst stimulation (iTBS) in ameliorating chronic nonfluent aphasia and compared it with that of LF-rTMS. Methods We randomly assigned patients with poststroke nonfluent aphasia to an ipsilesional iTBS (n = 29), contralesional 1-Hz rTMS (n = 27), or sham (n = 29) group. Each group received the rTMS protocol executed in 10 daily sessions over 2 weeks. We evaluated language function before and after the intervention by using the Concise Chinese Aphasia Test (CCAT). Results Compared with the sham group, the iTBS group exhibited significant improvements in conversation, description, and expression scores (P = .0004–.031), which characterize verbal production, as well as in auditory comprehension, reading comprehension, and matching scores (P < .01), which characterize language perception. The 1-Hz group exhibited superior improvements in expression, reading comprehension, and imitation writing scores compared with the sham group (P < .05). The iTBS group had significantly superior results in CCAT total score, matching and auditory comprehension (P < .05) relative to the 1-Hz group. Conclusions Our study findings contribute to a growing body of evidence that ipsilesional iTBS enhances the language recovery of patients with nonfluent aphasia after a chronic stroke. Auditory comprehension was more preferentially enhanced by iTBS compared with the 1-Hz protocol. Our findings highlight the importance of ipsilesional modulation through excitatory rTMS for the recovery of nonfluent aphasia in patients with chronic stroke.